Corporate Liability on the Crime of Producing, Distributing, and Utilizing Non-Standard Vaccines - Achmad Ardiansyah Akbar (Fakultas Hukum Universitas Hang Tuah, 2017)
Immunization is a mandatory program by government for every child in Indonesia. In 2016, however, the vaccine used for children‟s immunization was found under standardized or unqualified. It was mixed with particular substances which might lead the users into some allergies, minor or severe injuries, trauma, and even danger their lives. Parents certainly fully entrusted their children‟s immunization to the competent. The crime of producing, distributing, and using non-standard vaccines involved many parties both individuals and corporations, ranging from the task of producing, distributing, and up to injecting the vaccines into children. With the enormous profits of the crime, however, only private parties were sued while the corporations were still free from any accusation and thus, it made them have potential chances to redo such crime, violating medical laws, consumer protection laws, Money laundering legislation, and up to brand and geographical indications. This study was a legal research with statute and conceptual approaches. It aimed to investigate the provisions of producing and distributing non-standard vaccines by corporations and to analyze their liability on such crime. The results, conclusions, suggestions, and recommendations for the problem were discussed.